Dakwah Moderat Habib Muhammad Luthfi Bin Yahya di Dunia Virtual Analisis Wacana Teks Media Teun A. Van Dijk - Abdul Muhid; Samsuriyanto Samsuriyanto (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper aims to describe the results of moderate dakwah analyzes that discourse Habib Muhammad Luthfi bin Yahya in the virtual media. Through the virtual media, Habib Luthfi has been conducting dakwah activists in spreading Islamic moderation values ​​so as to create harmony in the life of society and to showcase Islam of rahmatan lil ‘alamin. The analytical technique used in this paper uses discourse analysis of media text of Teun A. Van Dijk, that is analyzing media text discourse by connecting text and context through social cognition of text maker. The study findings show that the moderate dakwah of Habib Muhammad Luthfi bin Yahya in the virtual media presents the face of Islam that does not teach excessive in every way, and always balanced and fair in looking at human beings. He urges Muslims not to fight against each other, not to mutually abuse each other, but instead to invite Muslims to strengthen brotherhood among human beings.